Предмет: Математика,
автор: svetamail
(42 : 6* 5 : 7 * 2) + 64=
(19 – 3 * 4 : 6 + 13) : 10=
(48 + 52 – 64) : 6=
41 + 5 * 3 – 16=
100 – 27 : 3 – 43=
(43 – 2 * 9) : 5 + 6 * 5 : 3=
46 – 24 : 4 + 30=
52 + 16 : 8 – 2 =
(36: 6 + 48 : 8) : 2 =
90 : 10 * 3 – 17 =
Ответы
Автор ответа:
0
(42 : 6* 5 : 7 * 2) + 64=74
(19 – 3 * 4 : 6 + 13) : 10=3
(48 + 52 – 64) : 6=6
41 + 5 * 3 – 16=40
100 – 27 : 3 – 43=48
(43 – 2 * 9) : 5 + 6 * 5 : 3=15
46 –24 : 4 + 30=70
52 + 16 : 8 – 2 =52
(36: 6 + 48 : 8) : 2 =7
90 : 10 * 3 – 17 =10
Похожие вопросы